Continuation or Reinvention? Assessment and Prospects of the Internal and External Policies of the Anwar Administration in Malaysia - Zhao, Xinlei (Technium Social Sciences Journal, 2023)
With Anwar Ibrahim becoming the 10th Prime Minister of Malaysia, Malaysia has finally entered a new period after three years of "political crisis". At this stage, despite the new administration, Anwar is still facing various domestic and foreign crises and challenges, including weak economic development, a volatile domestic political situation, a growing racial crisis and conflicts and confrontations between major powers. The internal policy will focus on revitalizing the economy and settling the domestic political situation, while the external policy will continue with pragmatic diplomacy and balanced diplomacy among major powers, and the development of relations with China will be the top priority of the Anwar administration. However, whether such internal and external policies will help to achieve Anwar’s political goals and baggage still needs to be observed and analysed, and the fragile political base is also an unstable factor affecting the stability of the new Anwar administration.